Determinants of Employee Performance in Regional Government Inspectorates: The Role of Education and Training, Motivation and Work Discipline - Dwi Rahmawati; Marzolina Marzolina; Kurniawaty Fitri (Journal of Management Economics and Financial Accounting, 2025)
Employee performance is a crucial aspect that determines the quality of public services and the effectiveness of an organization, including government agencies. In the current era of globalization and the demands of modernization, employee performance is influenced not only by internal organizational factors but also by various external factors, such as education and training, motivation, and work discipline. In Indonesia, one government agency that plays a crucial role in monitoring and enforcing regulations is the Regional Inspectorate, including the Kampar Regency Inspectorate. As a supervisory element of local government, the Kampar Regency Inspectorate plays a crucial role in improving the effectiveness of its oversight of the quality of financial reports and the accountability of regional agency performance. This study aims to analyze the influence of education and training, motivation, and work discipline on employee performance at the Kampar Regency Inspectorate Office. This study used a quantitative approach with a survey method. The population in this study was all 64 employees at the Kampar Regency Inspectorate Office. The sampling technique used a census method, thus utilizing the entire population as the research sample. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of SPSS. The results of the study indicate that education and training (diklat), motivation, and work discipline simultaneously have a positive and significant effect on employee performance at the Kampar Regency Inspectorate Office. Partially, education and training (diklat) have a positive and significant effect on employee performance, motivation has no positive effect on employee performance, and work discipline has a positive and significant effect on employee performance. Motivation has no significant effect on employee performance at the Kampar Regency Inspectorate Office. This indicates that the level of employee work motivation, whether in the form of achievement motivation, work enthusiasm, recognition, or responsibility, has not significantly contributed to improving employee performance. The results of this study indicate that improving the quality of education and training, strengthening work motivation, and implementing good work discipline can improve employee performance.